The Effectiveness of Dynamic Assessment Strategies in Solving Math Word Problems Using Cultural context - Andi Saparuddin Nur; Khumaeroh Dwi Nuraini; Dian Mayasari (Technium Social Sciences Journal, 2023)
Math word problems are relevant to the cultural context, making it easier for students to gain meaning. However, the potential of students is different in solving math word problems. Dynamic assessment strategies can be a solution to differences in student learning potential. This study aimed to analyze the effectiveness of dynamic assessment strategies in solving math word problems using cultural contexts. This research was conducted on junior high school students with an experimental design. The sample selection was done by cluster random, namely the control and experimental classes. Data analysis using t-test and Cohen test. The findings of this study indicate that dynamic assessment strategies can foster students’ word problem-solving abilities with learning potential scores in the high category. Students in the experimental class could solve word problems better than the control class. Meanwhile, the effect size of the dynamic assessment strategy is in the high category. This research recommends that teachers use dynamic assessment to maximize students’ potential in solving math word problems.